2018
DOI: 10.1007/s10637-018-0587-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II trial of pemetrexed plus radiotherapy in elderly patients with locally advanced non-small cell lung cancer

Abstract: Background Radiotherapy (RT) is an effective treatment for elderly patients with locally advanced non-small-cell lung cancer (NSCLC); however, no clinical trials have investigated combination RT with pemetrexed (PEM) in chemotherapy-naive patients ≥71 years old. We conducted a phase I/II study to evaluate the appropriate PEM dose, efficacy, and safety of PEM plus RT in elderly patients. Methods Patients ≥71 years with performance status (PS) scores of 0-2 who had pathologically confirmed stage IIIA/IIIB NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Treatment completion was de ned as the receipt of at least ve doses of nab-paclitaxel plus carboplatin and 64 Gy of thoracic radiotherapy within 58 days from the start of treatment. We considered tolerability and safety to be the most important aspects for elderly Japanese patients because severe lung toxicities have been reported in these patients [11,12]. In addition, we considered that the regimen to be effective if the tolerability was the same as that of carboplatin/paclitaxel in non-elderly patients with locally advanced NSCLC [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment completion was de ned as the receipt of at least ve doses of nab-paclitaxel plus carboplatin and 64 Gy of thoracic radiotherapy within 58 days from the start of treatment. We considered tolerability and safety to be the most important aspects for elderly Japanese patients because severe lung toxicities have been reported in these patients [11,12]. In addition, we considered that the regimen to be effective if the tolerability was the same as that of carboplatin/paclitaxel in non-elderly patients with locally advanced NSCLC [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the high incidence of pulmonary toxicities or non-platinum chemotherapy regimen not adapted to durvalumab, neither of these treatments was further developed. In a study using chemoradiotherapy with pemetrexed, although the objective response of the primary endpoint was met with 80.5%, grade 3 or higher pneumonitis was observed in 8 out of 41 patients (19.5%) [12]. Therefore, it was concluded that chemoradiotherapy with pemetrexed should be prescribed to elderly patients with caution.…”
Section: Discussionmentioning
confidence: 99%